Profil Gaya Belajar Peserta Didik Kelas I SDN Panggung Lor Semarang - Trirahayu, Tiwi; Sumarno , Sumarno (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The effectiveness of students' learning is influenced by the learning styles adopted by each student. The ability of students to grasp learning materials is relatively low. In the actualization of learning by teachers, there is no diagnosis of the learning styles mastered by each student. Research shows the inclination of learning styles mastered by first-grade students at Panggung Lor Elementary School. This research is a descriptive qualitative study. The research subjects were first-grade students totaling 28 and first-grade teachers. The data analysis process used three stages: data reduction, data display, drawing conclusions, and data verification. Data collection was carried out through observation techniques, interviews, and documentation. The results showed that first-grade students have various inclinations of learning styles. 46% of students have a visual learning style, 32% of students lean towards auditory learning styles, and 22% of students have a kinesthetic learning style